Insight Under Scrutiny in the Court of Protection: A Case Law Survey - Gurbai, Sándor; Fitton, Emily; Martin, Wayne (Frontiers in Psychiatry, 2020)
The concept of patient insight, of a patient’s self-awareness of illness or impairment (and related issues), plays a significant role in clinical discourse and clinical practice. But what role does it play in the legal process, particularly when a patient’s decision-making capacity (or ‘mental capacity’) is in question? We report on a survey of 412 published judgments from the Court of Protection of England and Wales, published between 2007 and 2018. We found that the notion of patient insight played a role in 53 cases (13% of the total). We use a variety of techniques to provide a systematic profile of these ‘insight cases’. We provide a demographic profile of the patients whose insight is discussed (focusing on gender, age and diagnosis) and a professional profile of the expert witnesses who raise the issue of insight. We then deploy the technique of ‘logical geography’ to map the meaning of the term insight and the inferential patterns in which reports of patient insight are embedded. We point out that the published insight cases never explicitly define ‘insight,’ and that they include no reference to structured instruments or scales for the assessment of insight. We show that the concept of insight, as used in the Court of Protection, is not synonymous with the concept of agreement with a diagnosis of illness; this is at most one of a range of meanings that the concept carries. We show that, despite the fact that the presence or absence of insight is not itself a legal criterion for mental capacity, insightlessness does play a role, and sometimes a decisive role, in shaping findings as regards the presence or absence of mental capacity. Finally, we assess the extent to which expert testimony in the insight cases conforms to the insight-related recommendation of the recent NICE Guideline on Decision-Making and Mental Capacity.